2016
DOI: 10.1039/c6ob00925e
|View full text |Cite
|
Sign up to set email alerts
|

Fast regioselective sulfonylation of pyridine/quinoline N-oxides induced by iodine

Abstract: Fast sulfonylation of pyridine/quinoline N-oxides induced by iodine is demonstrated herein. The regioselective protocol occurs under metal-free conditions in a short reaction time (10 min), exhibiting high efficiency (up to 92% yield) and good compatibility (up to 33 examples). A gram-scale reaction was conducted with only a slight loss of production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…Control experiments were performed to understand the mechanism of the iodine‐catalyzed, oxysulfonylation reaction (Figure and Figure 4). Under aerobic conditions and at 1 atm, a near quantitative yield of 3aa was obtained from styrene 1a and tosyl hydrazide 2a .…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments were performed to understand the mechanism of the iodine‐catalyzed, oxysulfonylation reaction (Figure and Figure 4). Under aerobic conditions and at 1 atm, a near quantitative yield of 3aa was obtained from styrene 1a and tosyl hydrazide 2a .…”
Section: Resultsmentioning
confidence: 99%
“…Indole derivatives were not amendable to this procedure. Xiang and He respectively depicted the sulfonylation of heteroaromatic N‐oxides, which might use hypoiodites (generated in situ from [I] and oxidant) as a means of substrate activators. The I 2 /H 2 O 2 ‐promoted protocol accomplished in a short reaction time (10 minutes) and still worked in a gram‐scale (Scheme ).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…Subsequently, the effect of reaction media on the efficiency was surveyed. It was found that 1,2-dibromoethane (DBE) was the most suitable solvent for the present reaction, while other solvents gave lower yields or trace amount of 3 aa (entries [8][9][10][11][12][13]. To our delight, the desired 3 aa was formed in 91% yield without DBE but under otherwise optimal conditions (entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…Minisci-type radical addition [4] (Scheme 1b) pathway under metal-free conditions represents a highly attractive approach because of excellent regioselectivity and high efficiency. However, compared with the wellestablished functionalization of quinoline N-oxides activated by various electrophiles (sulfonyl chlorides, [5] acyl chlorides, [6] anhydrides, [7] PyBroP, [8] H-phosphonate, [9] iodine reagents, [10] boron reagents, [11] etc. [12] ), the regioselective nucleophilic substitution of Noxides activated by a free radical activator have not been reported.…”
Section: Introductionmentioning
confidence: 99%